ALDH1A3 Is the Key Isoform That Contributes to Aldehyde Dehydrogenase Activity and Affects in Vitro Proliferation in Cardiac Atrial Appendage Progenitor Cells - Puttini, Stefania; Plaisance, Isabelle; Barile, Lucio; Cervio, Elisabetta; Milano, Giuseppina; Marcato, Paola; Pedrazzini, Thierry; Vassalli, Giuseppe (Frontiers in Cardiovascular Medicine, 2018)
High aldehyde dehydrogenase (ALDHhi) activity has been reported in normal and cancer stem cells. We and others have shown previously that human ALDHhi cardiac atrial appendage cells are enriched with stem/progenitor cells. The role of ALDH in these cells is poorly understood but it may come down to the specific ALDH isoform(s) expressed. This study aimed to compare ALDHhi and ALDHlo atrial cells and to identify the isoform(s) that contribute to ALDH activity, and their functional role. Methods and Results: Cells were isolated from atrial appendage specimens from patients with ischemic and/or valvular heart disease undergoing heart surgery. ALDHhi activity assessed with the Aldefluor reagent coincided with primitive surface marker expression (CD34+). Depending on their ALDH activity, RT-PCR analysis of ALDHhi and ALDHlo cells demonstrated a differential pattern of pluripotency genes (Oct4, Nanog) and genes for more established cardiac lineages (Nkx2.5, Tbx5, Mef2c, GATA4). ALDHhi cells, but not ALDHlo cells, formed clones and were culture-expanded. When cultured under cardiac differentiation conditions, ALDHhi cells gave rise to a higher number of cardiomyocytes compared with ALDHlo cells. Among 19 ALDH isoforms known in human, ALDH1A3 was most highly expressed in ALDHhi atrial cells. Knocking down ALDH1A3, but not ALDH1A1, ALDH1A2, ALDH2, ALDH4A1 or ALDH8A1 using siRNA decreased ALDH activity and cell proliferation in ALDHhi cells. Conversely, overexpressing ALDH1A3 with a retroviral vector increased proliferation in ALDHlo cells. Conclusions: ALDH1A3 is the key isoform responsible for ALDH activity in ALDHhi atrial appendage cells, which have a propensity to differentiate into cardiomyocytes. ALDH1A3 affects in vitro proliferation of these cells.